2008
DOI: 10.1182/blood.v112.11.1984.1984
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Poor Outcome in Danaparoid-Treated HIT-Patients: A French Multicentre Case-Control Study.

Abstract: Objective: to identify predictive factors of complications and mortality in danaparoid-treated HIT-patients. Patients and Methods: case-control study involving HIT-patients defined by a relative decrease in platelet count of over 40% with or without thrombosis at presentation and positive laboratory testing (functional assay +/− ELISA). A patient presenting a complication 48 hours after heparin replacement with danaparoid (thrombosis, DIC, amputation, haemorrhage, death) was considered as a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We found 5 nonrandomized studies that reported on DVT outcomes in patients with confirmed HIT. 17,19,65,75,76 Three cohort studies reported on symptomatic lowerextremity proximal DVT. 17,19,75 One study reported on symptomatic upper-extremity DVT.…”
Section: Recommendation 37bmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 5 nonrandomized studies that reported on DVT outcomes in patients with confirmed HIT. 17,19,65,75,76 Three cohort studies reported on symptomatic lowerextremity proximal DVT. 17,19,75 One study reported on symptomatic upper-extremity DVT.…”
Section: Recommendation 37bmentioning
confidence: 99%
“…19 Two cohort studies reported on asymptomatic HIT patients who were screened for silent DVT. 65,76 The EtD framework is shown online at https://dbep.gradepro.org/profile/ 52FE6F09-0233-F65B-BA7A-5ADB96E1007D.…”
Section: Recommendation 37bmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin-induced thrombocytopenia (HIT) is an iatrogenic disorder characterized by thrombocytopenia and a high risk of limb-or lifethreatening thrombosis. [1][2][3] Pathogenic HIT antibodies react with a multimolecular complex of platelet factor 4 (PF4) and polyanions such as heparin or cell-surface glycosaminoglycans. 4,5 Immuglobulin G-containing immune complexes involving PF4 bound to membrane chondroitin sulfate (CS) activate platelets through FcgIIA receptors, 5,6 contributing to the risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…These atypical sites of thrombosis in VITT stand in distinction to those in HIT and aHIT, where thromboses occur in more typical locations, such as deep venous thrombosis, pulmonary embolism, and/or arterial thromboses. [29][30][31][32] The laboratory features of VITT indicate a consumptive coagulopathy (thrombocytopenia, low fibrinogen, and elevated Ddimer), which is only seen in the most severe cases of HIT. 33 When performed, tests for acquired thrombophilias such as antiphospholipid antibodies, paroxysmal nocturnal hemoglobinuria, ADAMTS13 deficiency, and myeloproliferative neoplasms are usually normal.…”
Section: Vitt Is Pathogenically Linked To Autoimmune Heparin-induced Thrombocytopeniamentioning
confidence: 99%